Frequency of Vitamin B12 Deficiency Among Type 2 Diabetes Mellitus Patients Presenting at a Tertiary Care Hospital - Alam, Said; Khan, Nisar; Khan, Imran Ullah; Zia, Abduulah; Shafiq, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Vitamin B12 deficiency is a recognized metabolic complication among patients with type 2 diabetes mellitus, potentially contributing to neuropathy and haematological abnormalities. Limited regional data exist regarding its burden in routine clinical practice. Objective: To determine the frequency of vitamin B12 deficiency among type 2 diabetes mellitus patients presenting at a tertiary care hospital. Methods: This study included 194 T2DM patients aged 25 to 70 years. T2DM was defined as elevated fasting blood glucose (≥126 mg/dL), HbA1c (≥6.5%), or a 3-year history of antidiabetic medication use. Patients with parathyroid disorders, pre-existing renal disease, and chronic liver disease were excluded. Patients were assessed for Vitamin B12 deficiency (B12 levels < 200 pg/mL). Data was analyzed using SPSS 26. Vitamin B12 deficiency was presented as frequencies and percentages. Stratifications were performed using the chi-square test, with P values < 0.05 considered significant. Results: The mean age of 194 patients with T2DM was 50.98±11.99 years. The study had 105 (54.1%) males and 89 (45.9%) females. Eighty-three (42.8%) patients had hypertension, 76 (39.2%) were smokers, and 138 (71.1%) had BMI >24.9 kg/m². The frequency of vitamin B12 deficiency was 15.5% (n=30). Patients aged 55 years or older had the highest frequency of deficiency, but this association was not significant (P = 0.06). Conclusion: This study found a moderate prevalence of vitamin B12 deficiency in type 2 diabetic patients (15.5%). In older patients, the frequency of deficiency was higher, but not significant.